Optimalisasi Pembelajaran Al-QurÔÇÖan Melalui Metode YanbuÔÇÖa di Madrasah Ibtidaiyah - Sela Septiani; Miftahul Janah; Muzawir Munawarsyah; Mahmud Arif (IAIN Batusangkar, 2024)
Seeking knowledge of the Quran is a task commanded by Allah SWT. Observing the current situation, where many students do not yet have adequate skills in reading the Quran, let alone understanding it. So that is the reason why it is important to use effective methods in the learning process. There are various effective methods in the process of teaching reading the Quran, one of which is the yanbu'a method. The aim of this research is to describe the optimization of the Quran learning through the yanbu'a method in Madrasah Ibtidaiyah. This research used library research. Data collection used secondary data sources. When reading the Quran, Muslims are required to read it fluently and accurately. Yanbu'a is a method applied to learn how to read, write and memorize the Quran in a structured and easy to implement manner. Optimizing the Quran learning through the yanbu'a method in Madrasah Ibtidaiyah, namely training for teachers, the yanbu'a method which is taught in a structured manner, giving awards to students, and support from parents. The yanbu'a method allows students to study the Quran systematically starting from the basic stage so as to build a strong foundation in understanding the reading of the Quran.